An Evaluation of Global Publications of Geothermal Energy Research: A Bibliometric Review - Poornima, A; Deepika, R; Ravi, S (Journal of Data Science, Informetrics, and Citation Studies)
The study examines global “Geothermal Energy” research on a set of quantitative and qualitative metrics to understand the status of research in the subject at a global level. The study analysis is based on publication data on the subject, comprising a total of 492 publications as indexed in the Web of Science database covering the period 2014-2024. The study provides a window of annual scientific production, the most productive authors, journals, keywords, trends, hot topics, organizations, countries, thematic and conceptual country collaboration maps, and highly cited references in the context of collaborative research. The study finds that the number of publications in this field has increased steadily, with the most significant growth occurring in the past decade. Dincer I, is the most proactive author, with an h-index of 5 and 261 citations. The most frequently used keywords in “energy” are 73 (7%), followed by “performance” at 69 (6%). The most productive trends in the hotspot “fluid” and “geochemistry” and constraints” are, respectively, term frequency. The top journals in this field include Energies (58), Citescore (6.2), and impact factor (3.0). China has leading organizations in the field of geothermal energy research. This study has evaluated the growth and impact of geothermal energy research across the globe from 2014 to 2024. The study also helps the researchers and relevant stakeholders with a starting point to further maximize research and research networks in critical and advanced areas of research in the field of geothermal energy research.
Keywords: Geothermal Energy; Bibliometrix; Scientometrics; Bibliometrics; Energy Research.